Primary mediastinal seminoma with leiomyosarcoma: a rare case report - Qi, Yali; Dong, Chi; Cui, Wenjun; Da, Lijun; Li, Enxi; Liu, Yating; Song, Feixue (Cellular and Molecular Biology, 2022)
Germ cell tumor is the most common malignant tumor of the gonads, sometimes they are found in locations other than the gonads, called Extra-gonadal Germ cell tumours (EGCTs). Primary mediastinal germ cell tumors (PMGCTs) are a kind of rare neoplasm in the anterior mediastinum, including seminoma and non-seminomatous, or appear as a mixture. Primary mediastinal seminoma mixed with sarcoma is an extremely rare clinicopathologic entity. Previous studies have revealed that primary pure mediastinal seminomas are commonly sensitive to chemoradiotherapy and possibly to palliative excision. The treatment options for mixed germ cell tumor composed of seminoma and sarcoma remain unknown. Only one case of primary mediastinal seminoma with rhabdosarcoma has been reported in the literature up to date and the patient benefited from chemotherapy as the neoadjuvant therapy. However, cases of primary mediastinal seminoma with leiomyosarcoma have not been documented. Herein, we report a case of an 18-year-old patient, who presented with dyspnea, orthopnea, and chest pain, the CECT scan of the chest showed a large mass in the anterior mediastinum, which turned out to be seminoma mixed with leiomyosarcoma after partial excision. We investigate the treatment strategy and potential molecular mechanism of this disease. Finally, our study demonstrated that the patient benefited from the treatment of chemotherapy alone, or combined with target therapy after the operation. Meanwhile, the BRAF p.G466V, TP53 mutations, MTOR p.T1977I and exons 2-5 deletion of FLCN may be potential molecular mechanisms and oncogenic drivers of this disease.